QUALITY CONTROL PROFILING, ANTIFUNGAL AND IN VIVO CYTOTOXIC POTENTIAL OF ORIGANUM MAJORANA L. - PREETHY ANN MATHEW; M. NALINI PADMANABHAN (International Journal of Pharma and Bio Sciences, 2015)
Phytochemicals in various extracts and essential oil of Origanum majorana L. were screened. In addition, the pharmacognostic profile of leaf powder and essential oil were investigated in order to develop standards for identification and quality control. The findings confirmed for presence of maximum number of phytoconstituents such as carbohydrates, proteins, amino acids, saponins, flavonoids, alkaloids, phenolic compounds, vitamin C and tannin in aqueous extract whilst essential oil possessed only volatile oils, flavonoids and phenols. Subsequent investigation of antifungal potency showed efficacy of essential oil against all the tested pathogens: Aspergillus flavus > A. niger > Candida albicans > A. fumigatus > A. terreus > Penicillium notatum. Brine shrimp lethality assay performed to evaluate the cytotoxicity of all extracts and essential oil exhibited no deleterious toxic effects. These findings, clearly suggest that O. majorana essential oil can be used in quality control of fungi, especially the tested organisms in the present study.